DAYA TERIMA BISKUIT DENGAN MODIFIKASI TEPUNG BIJI NANGKA, TEPUNG KACANG MERAH DAN TEPUNG PISANG SERTA KONTRIBUSINYA TERHADAP KECUKUPAN ENERGI, PROTEIN DAN ZAT BESI REMAJA - citra chairannisa; Albiner Siagian; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT Jackfruit seeds,red beans and banana flour can be processed into various food product which can give contribute nutrient, like energy, protein and iron. One of the product is biscuits. This study was aimed to determine the acceptability which comprised the color, flavor, taste and texture which were tested by hedonic test and the contribution to adequacy of the energy, protein, and iron. This was an experimental study on making biscuits by adding Jackfruit seeds, red beans and banana flour in different proportion of Jackfruit seeds, red beans and banana flour (7:4:4, 4:7:4 and 4:4:7). Organoleptic test of modified biscuits was given to thirty panelist of students in The Faculty of Public Health,University of Sumatera Utara. Analyzed was done descriptively. The results of this research showed that by organoleptic test of color, flavor and texture, biscuits with the addition of Jackfruit seeds, red beans and banana flour which made with 4:4:7proportion was the favored by the panelists. Based on the analysis of variance, the modification of Jackfruit seeds, red beans and banana flour in different proportion influenced different variety of taste, flavor and texture. The addition of Jackfruit seeds, red beans and banana flour on biscuit making increased the content of iron and protein. Consumption of five pieces A2 biscuits with addition Jackfruit seeds, red beans and banana flour contributes 15,7%, 14,7% and 18,7% adequacy of energy, protein and iron in 16-18 years adolescent boy and 19,8%, 16,5% , 10,8% adequacy of energy, protein and iron in 16-18 years adolescent girl. It is suggested for consumer to make biscuits with addition Jackfruit seeds, red beans and banana flour as an alternative health food to adequacy of the energy, protein and iron for adolescent. In addition it is necessary to do other foods diversification by added Jackfruit seeds, red beans and banana flour as a food which is rich in nutrient content